Meningkatkan Kemandirian Belajar Siswa Materi Manusia Makluk Pribadi Melalui Model PBL Fase E SMK Negeri 2 Tuhemberua - Darmawati Gulo (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education in Indonesia is currently the focus of urgent attention in efforts to improve the quality of national education. There is an urgent need to increase student independence as a necessary preparation for facing increasingly complex future challenges. The new policy in improving the quality of Indonesian education was carried out with a new breakthrough in creating an independent learning curriculum policy initiated by the Minister of Education and Culture Nadiem Makarim. The objectives to be achieved in this study are to know the increase in student learning independence in PAK material human beings personal beings through the use of problem based learning learning models. Studied, namely the independence variable and the learning achievement variable obtained from the learning achievement test from the end of cycle 1 and cycle 2. From the results of data analysis it appears in the results of cycle I and cycle II, that through the application of the Problem Based Learning model in an effort to increase student independence, experience improvement in the level of completeness. Where the completeness level of the independence dimension in cycle 1 only reached 69% in the feasible category, while the completeness level of independence in cycle II experienced an increase, reaching 92% in the proficient category. The use of the PBL learning model can increase the independence and achievement of student learn